Foraging strategies and foraging plasticity in harvester ants (Pogonomyrmex spp., Hymenoptera: Formicidae) of the central Monte desert, Argentina - Pol, Rodrigo Gabriel (2015)
Foraging strategy determines the way harvester ants use space and therefore their access and impact on seed resources. In this study, we described the foraging strategy of three sympatric South American species of Pogonomyrmex ants to confirm that they are solitary foragers as is suggested anecdotally in the literature. Then we tested whether those foraging strategies are fixed or flexible in response to seed density and distribution. Based on individual and group movements of foraging ants, we determined that P. rastratus MAYR, 1868 is exclusively a solitary foraging species, P. inermis FOREL, 1914 use a group-foraging strategy with limited recruitment, and P. mendozanus CUEZZO & CLAVER, 2009 displays an intermediate foraging system in which workers are typically solitary foragers but also recruit nestmates to highdensity seed patches. The addition of seeds near the nest modified the foraging behavior of the three species by different amounts. Individual foragers of each species reduced their search time and search area, and colonies increased their foraging activity rate, probably as a result of a higher returning rate of successful foragers after seed addition. Such behavioral responses were much more conspicuous in P. mendozanus than in the other two species. Flexibility in foraging and diet breadth reported for some of these harvester ants may constitute important adaptive features in the central Monte desert where seed abundance is highly heterogeneous, irregular, and severely affected by anthropic disturbances.